Reconstruction and Development Programme as a Tool of Socio-economic Transformation in South Africa - Aneta Křičková (Modern Africa, 2015)
The article offers an overview of the post-apartheid development  in South Africa with a special focus on a policy promoted by the  African National Congress (ANC) to mitigate socio-economic inequality  within South African society. In this sense, the key strategy of the ANC  was the economic platform, of which the goal was to achieve poverty  reduction and the strengthening of the economy. For this purpose the  Reconstruction and Development Programme (RDP) was adopted in  1994. The main aim of the article is the ANC’s strategy in the field of  the RDP that can be considered the specific tool of socio-economic  transformation because the RDP was essentially a basic-needs programme  which focused on the provision of infrastructure, housing,  free and compulsory schooling, electricity, running water and toilets,  health care and land to the poor.